Transformasi Subjek dalam Monolog Balada Sumarah: Perspektif Teori Slavoj Žižek : Subject Transformation in the Monologue of Balada Sumarah: The Perspective of Slavoj Žižek's Theory - Rinda Widya Ikomah; Aliurridha Aliurridha; Rahmin Meilani Putri (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study examines the transformation of the character Sumarah in the monologue Balada Sumarah by Tentrem Lestari, drawing on Slavoj Žižek's theory. The main focus of this study is to analyze external factors, moments of emptiness, and radical actions that occur in the process of changing the symbolic order experienced by Sumarah. The purpose of this study is to understand how external events, such as the social stigma and rejection she faces, shape her awareness and radical actions as an effort to liberate herself. The method used is a qualitative approach with literary analysis, which connects Žižek's theory on the symbolic order, emptiness, and the radicalization of the subject. The results of the study show that the change in the symbolic order experienced by Sumarah is influenced not only by external factors but also by moments of emptiness that give rise to a deep awareness that drives radical actions. In conclusion, the murder committed by Sumarah is a form of self-liberation from an oppressive social order. Recommendations for further research include exploring the application of Žižek's theory to literary characters, especially monologues, and the social implications of radical actions in a literary context.